METODOLOGI PENDIDIKAN ISLAM PERSPEKTIF AL-GHAZALI - Oktavia, Eka; Himmah, Aliyatul; Santika; Siregar, Wanidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is a crucial component of life and has been a topic of discussion among scholars, including Imam al-Ghazali. This research examines the methodology of Islamic education from al-Ghazali's perspective. The results indicate that al-Ghazali's educational methodology emphasizes religious and moral education. He argues that the goal of Islamic education is to form a perfect human being. Al-Ghazali's thoughts lean towards education in faith, morals, intellect, social aspects, and physical well-being. In curriculum development, al-Ghazali adopts two approaches: religious and pragmatic. According to his perspective, Islamic education materials include faith education, moral education, intellectual education, social education, and physical education. Al-Ghazali stresses that a good teacher must be intelligent, wise, and possess commendable qualities. Meanwhile, students should be humble, cleanse themselves of bad traits, be obedient, and maintain consistency. Educational evaluation encompasses all activities related to responsibility in the educational process. This research provides insights into al-Ghazali's educational methodology in achieving national education goals, considering the challenges of evolving times and other influencing factors.